Sport experiences of Division I collegiate athletes and their perceptions of the importance of specialization - Martin, E. M.; Ewing, M. E.; Oregon, E. (High Ability Studies, 2017)
The purpose of the current study was to investigate Division I athletes` prior sport participation and athletes` perceptions regarding sport specialization. Athletes (N = 1041) completed self-report surveys and indicated that participation in their collegiate sport began around nine years of age (M = 9.10, SD = 3.83). Athletes played a large number of sports in elementary and middle school with participation decreasing during high school. For those athletes who specialized in one sport, specialization occurred typically at 12.5 years of age. In addition, athletes past sport background and perceptions of specialization differed depending on their college sport with some sports (i.e., gymnastics) starting participation and specializing earlier than others (i.e., football, cross country, and track and field). Interestingly, no differences existed in past sport experiences or perceptions of specialization dependent on scholarship status or expected playing status. This study supports prior research that early specialization is not a requirement for elite level performance.